Ecobrick Sebagai Solusi Dinding Nonstruktural Ramah Lingkungan: Ecobrick As an Eco-friendly Nonstructural Wall Solution - Fazrina Andriani Sakinah Lubis; Erizal (Departemen Teknik Sipil dan Lingkungan, IPB University, 2021)
Population growth increased in the need for dwelling which impacted to high demand for bricks. However, bricks have a negative impact on the environment due to the materials and the production prosses. Population growth also effected an increase amount of plastic waste that has a risk to the health and environment. This research aimed to analyze the compressive and flexural strength of brick and ecobrick (PET bottle filled with plastic waste) wall, to know degree of difference in strength between both wall, and to compare the cost of making the wall. This research was started from preparation, manufactured, cured, and tested the specimens. The cost analysis refers to the Bogor district in 2019. The result was obtained compressive strength of brick is higher than ecobrick, which is brick 2,38 MPa and ecobrick 1,31 MPa. Flexural strength of ecobrick is higher than brick, which is ecobrick 1,23 MPa and brick 1,18 MPa. T-test show that compressive strength both wall is significantly different, while the flexural strength both wall is not significantly different. The cost of making ecobrick walls is 20% cheaper than brick walls.